Spectral features of nasals in Standard Latvian - Taperte, Jana (Baltistica, 2015)
In the article, the acoustic features of nasals in Standard Latvian are investigated. The aim of the study is to examine whether some of the spectral properties of nasal murmur (namely anti-formant frequency, as well as frequency and bandwidth of the first nasal formant) can be considered as efficient cues for distinguishing between nasal places of articulation. Speech recordings from 10 native speakers of Standard Latvian, five male and five female, aged 19–39, without any disorders or dialectal traces in their pronunciation, were used for the analysis. Prevocalic nasals [m; n; ɲ] were analyzed in isolated CVC syllables, where C is one of the nasals and V is one of the vowels [i(ː); e(ː); æ(ː); ɑ(ː); ɔ(ː); u(ː)]. The velar [ŋ] — the allophone of the phoneme /n/ — was recorded in postvocalic position in [k]V[ŋks] structure units. 1260 items were analyzed in total. According to the results, the nasals of Standard Latvian can be distinguished by anti-formant frequencies rather efficiently, and the results generally agree with those obtained in previous research of Latvian as well as data reported for other languages. The frequencies and the bandwidths of the first nasal formant are less informative regarding nasal place of articulation and can be used only for distinguishing between [ŋ] and [m; n; ɲ]. Conducting perception tests to assess the auditory relevance of these acoustic features is necessary.